Investigation of Technology Usage and Its Impact on Business Sustainability of Micro Entrepreneurs in Salem District - M. Ravikumar; Dr. S. Deepa (IJRDO - Journal of Business Management, 2025)
The advent of digital technology has reshaped the operations systems of micro enterprises by redefining the communication, transaction, and resource management processes between entrepreneurs. The present study examines the level of utilisation of digital technology by micro entrepreneurs in Salem District considering the identification of the levels of adoption, operational barriers and consequent improvement in their business. The research design is empirical research work with the use of primary data obtained from 223 respondents using structured interview schedule. The research uses systematic random sampling in order to ensure representativeness across retail, service and small scale manufacturing sectors. The study used advanced analytical tools like K-Means clustering, Conjoint Analysis and Canonical Correlation The analysis are used to understand usage patterns and relationships between adoption behaviour and business outcomes. The findings show digital technology has become a crucial enabler of efficiency but the adoption of the technology is still uneven across sectors. The micro-entrepreneurs are highly willing to use digital tools while struggling in terms of cost, infrastructure and digital literacy.